Faktor-Faktor yang Mempengaruhi Struktur Modal Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - MUHAMMAD SYAHRIL FERDIANSYA; ISNURHADI . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
The purpose of this research is to investigate the factors (i.e profitability, free cash flow, business risk and liquidity) effecting the capital structure companies in Â mining sector listed in Indonesian Stock Exchange.The population of mining sector is 30 companie. Due to data availability only13 companies are selected as a sample. Using multiple regression method, data are analized and interpreted. The result shows that simultaneously profitability, free cash flow, business risk and liquidity have significant effect on the capital structure. Partially, free cash flow, business risk and liquidity have significant effect on capital structure,while profitability does not. The model is able to explain the variability of dependent variable as much as 13,7% whereas the remaining 86,3% can be explained by other factors which is not included in the model.